OPTIMALISASI PEMASARAN JASA PENDIDIKAN ISLAM MELALUI COMPETITIVE STRENGTH DAN COMPETITIVE RESULT - ambar wati (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2022)
Marketing strategy is an activity to find ways to achieve profitable exchange rates with targeted customers to achieve the goals of Islamic educational institutions. If an educational institution wants to provide a good image to attract consumers, then logically, educational institutions must develop different marketing strategies so that customers are interested in using the institution's services. The form of marketing responsibility is that educational institutions must work as hard as possible to manage and improve the quality of education that is promoted to the public. These qualities can be in the form of a competitive advantage which means the extent to which an organization is able to create a position and can maintain the market as long as there are competitors. These competitive advantages include competitive strength in the form of additional development of educational service products, the supply of power for users of educational services, the potential for entry of new entrants to educational institutions, the strength of supply from educational institutions,  and competition between educational institutions. The competitive result from educational institutions is competent graduates in accordance with the expectations of skill competencies. In general, the competencies expected of graduates from an educational institution are to have two sides of expertise, namely hard skills and soft skills.